How Well Do Caregivers Detect Depression and Anxiety in Patients With Parkinson Disease?. (September 2018) - Kua, Zhong Jie; Pachana, Nancy A.; Byrne, Gerard J.; O'Sullivan, John D.; Marsh, Rodney; Torbey, Elizabeth; Silburn, Peter A.; Mellick, George D.; Dissanayaka, Nadeeka N. W.
Depression and anxiety are prevalent in Parkinson disease (PD) yet underrecognized in clinical practice. Caregiver reports are frequently utilized to aid in the assessment of neuropsychiatric symptoms but little is known about caregivers' ability to recognize them in patients with PD. This study sought to examine the accuracy of caregiver reports. Eighty patient–caregiver dyads were involved. Accuracy of caregiver recognition was assessed by examining the level of agreement between caregiver ratings on the Neuropsychiatric Inventory and patients' diagnosis of depression and anxiety on the Mini-International Neuropsychiatric Interview (MINI)-Plus. The agreement between caregiver report and MINI-Plus diagnosis was low for both depression (6.3%) and anxiety (17.5%). The presence of depression was overreported, while anxiety was largely underestimated by caregivers. Caregiver distress significantly predicted inaccurate caregiver identification of depression ( R 2 = .51, P < .001) and anxiety ( R 2 = .08, P < .05). Results indicate that caregivers may be poor at recognizing depression and anxiety in patients with PD. Utilization of caregiver report should take into account potential biases that affect caregiver judgment.